Effects of spiritual intelligence on leadership effectiveness mediated by ethical behaviour: a conceptual analysis - Osman-Gani, Aahad M.; Anwar, Md. Aftab (2014)
Management and Leadership scholars are looking for new ideas and interventions that would have significant effects on corporate leaders in overcoming the ethical lapses that were observed in recent times. In this regard, positive and higher levels of spirituality and religiosity were found to help in controlling greed and reducing ethical-moral violations leading to improved performance of organizational leaders (Osman-Gani, Hashim & Ismail, 2013; Osman-Gani & Sarif, 2011). Spiritual intelligence is another dimension of human capability that is related to individual level of Spirituality, and this has recently become an important research topic for investigating its effects on individual and organizational performance. Leadership effectiveness is the measurement of leader’s performance effectiveness in relation to his/her abilities to the achievement of individual and organizational goals. Management and leadership scholars have found that human-centred organizations give more emphasis on doing meaningful work and on improving employee self-esteem, expectation, contentment and personal development through the directions of effective leaders (Rego & Cunha, 2008). This paper presents a conceptual analysis in identifying the effects of spiritual intelligence on leadership effectiveness, and in linking the mediating effects of ethical behaviour in this relationship. The analysis based propositions may trigger more research interests in this area leading to increased empirical studies in future, findings from which will help organizations to develop relevant policies and strategies in nurturing and developing spiritual dimensions of leaders and employees.